Aplikasi Berbasis Word Wall pada Pembelajaran Bahasa Indonesia - Wini Sugiani (Jurnal Guru Indonesia, 2022)
AbstractThe problem that occurs in the field is that students' ability to analyze the elements of poetry is still low because students are not aware of the influence of figures of speech in poetry. In addition, the selection of teaching materials for the appreciation of literature is largely determined by the teacher's ability to analyze literary works. The general aim of this study is to find out the elements of the figurative language contained in Chairil Anwar's poem Senja di Pelabuhan Kecil as a means of enriching the intellectual insights of readers which can later be expressed in the form of appreciation of literary works and the creation of literary works. This research is qualitative, namely using descriptive-analytic research methods. The results of the study show that the use of a figure of speech has an important role because poetry is the embodiment of the poet's soul contained in the language medium. Even the figure of speech itself is often seen as a characteristic of a type of literature called poetry, although not all poetry features a figure of speech, in most of the poems, including the poem Senja di Pelabuhan Kecil, the use of a figure of speech is considered to be very supportive of poetic means and arrangement of meaning. The implications of this study refer to the possibility that the results of this study can be applied in the field. The study of the figurative language elements of Senja di Pelabuhan Kecil by Chairil Anwar can be used as teaching material for Literary Appreciation based on its relation to the criteria of teaching materials. AbstrakMasalah yang terjadi di lapangan adalah kemampuan siswa dalam menganalisis unsur-unsur puisi masih rendah karena siswa kurang menyadari pengaruh majas dalam puisi. Selain itu, pemilihan bahan ajar apresiasi sastra sangat ditentukan oleh kemampuan guru dalam menganalisis karya sastra. Tujuan umum penelitian ini  untuk mengetahui unsur majas yang terdapat dalam puisi Senja di Pelabuhan Kecil karya Chairil Anwar sebagai sarana memperkaya wawasan intelektual pembaca yang nantinya dapat dituangkan dalam bentuk apresiasi karya sastra maupun penciptaan karya sastra. Penelitan ini besrsifat kualitatif, yaitu menggunakan metode penelitian deskriptif analitik. Hasil penelitian menunjukkan penggunaan majas memiliki peranan yang cukup penting karena puisi itu merupakan perwujudan jiwa penyair yang tertuang dalam media bahasa. Bahkan majas sendiri sering dipandang sebagai ciri khas bagi jenis sastra yang disebut puisi, meskipun tidak semua puisi menampilkan majas, namun pada sebagian besar puisi termasuk puisi Senja di Pelabuhan Kecil ini, penggunaan majas dianggap sangat menunjang bagi sarana kepuitisan dan  susunan makna. Implikasi dari penelitian ini merujuk pada kemungkinan bahwa hasil penelitian ini dapat diterapkan di lapangan. Pengkajian terhadap unsur majas puisi Senja di Pelabuhan Kecil karya Chairil Anwar ini dapat dijadikan sebagai bahan ajar Apresiasi Sastra berdasarkan kaitannya dengan kriteria bahan ajar.